Nonlinear dynamics of a distributed feedback interband cascade laser subject to optoelectronic feedback - Zhao, Maorong; Xia, Guangqiong; He, Chaotao; Wang, Qiupin; Kang, Ziyi; Ou, Pu; Liu, Junqi; Liu, Shuman; Wu, Zhengmao (Optics and laser technology, 2025)
Nonlinear dynamics of a distributed feedback interband cascade laser (DFB-ICL) subject to optoelectronic feedback (OEF) are experimentally investigated by analyzing the time series and power spectra in this work. The results demonstrate that under a fixed bias current, diverse nonlinear dynamical states including regular pulsing, quasiperiodic pulsing, two-frequency quasiperiodic pulsing, and two types of periodic pulsing oscillations can be observed via varying the feedback strength. For different bias currents, the evolution routes of nonlinear dynamical states in the DFB-ICL under OEF with feedback strength are examined by the power spectra mappings. Moreover, a mapping of the dynamical states in the parameter space of bias current and feedback strength is presented. This work would be helpful to better understand the nonlinear dynamics of DFB-ICL under OEF.